Heavy Metal Complexes of 1, 2, 3-Triazole derivative: Synthesis, Characterization, and Cytotoxicity Appraisal Against Breast Cancer Cell Lines (MDA-MB-231) (Baghdad Science Journal, 2022)
New chelating ligand derived from triazole and its complexes with metal ions Rhodium, Platinum and Gold were synthesized. Through a copper (I)-catalyzed click reaction, the ligand produced 1,3-dipolar cycloaddition between 2,6-bis((prop-2-yn-1-yloxy) methyl) pyridine and 1-azidododecane. All structures of these new compounds were rigorously characterized in the solid state using spectroscopic techniques like: 1HNMR, 13CNMR, Uv-Vis, FTIR, metal and elemental analyses, magnetic susceptibility and conductivity measurements at room temperature, it was found that the ligand acts as a penta and tetradentate chelate through N3O2, N2O2, and the geometry of the new complexes are identified as octahedral for (Rh & Pt) complexes and for (Au) complex square planner. The newly prepared compounds were designed and efficiently synthesized to be used to investigation of their toxicity bioassay (in vitro) as anticancer agent towards MDA cell lines. From the results obtained from cytotoxic assay, it can be concluded that the synthesized compounds are promising as new anticancer candidates in future especially in high concentration.